Urinary tract infections and dietary supplements: counselling in pharmacy - Novais, Marta (2018)
Urinary tract infections (UTIs) are some of the most common bacterial infections. Treatment usually involves antibiotics, and recurrence is a major concern. Therefore, identifying new and effective strategies, like the use of botanical dietary supplements, to control UTIs is a high priority. It is also important to provide health professionals with adequate knowledge related to the use of dietary supplements and other complementary and/or alternative medicines.